Shadow [videorecording (DVD)] - Zhang, Yimou; Zhang, Yimou; Deng, Chao, 1979-; Sun, Li, 1982-; Zheng, Ryan (Well Go USA Entertainment, 2019)
A military commander has the secret weapon known as a "shadow" which creates a look-alike who can fool his enemies.